Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar IPS Siswa Kelas IV SD Negeri 097325 Bandar Siantar - Elprida Kristina Silalahi; Jumaria Sirait (Journal on Education, 2023)
This study aims to determine whether the Problem Based Learning (PBL) Learning Model Affects the Learning Outcomes of Class IV Students in Subtheme 3 Learning "Gratitude for Diversity" at SD Negeri 097325 Bandar Siantar exists or not. There are 2 hypotheses in the study, namely, (1) there is an effect of applying the Problem Based Learning (PBL) model on the learning outcomes of Grade IV students in subtheme 3 learning "Gratitude for Diversity" at SD Negeri 097325 Bandar Siantar (H1) and there is no effect of applying the model Problem Based Learning (PBL) on Class IV Student Learning Outcomes in Subtheme 3 Learning "Gratitude for Diversity" at SD Negeri 097325 Bandar Siantar (Ho).This research method is an experimental method with the type of pre-experimental design that uses the One Group Pretest-Posttest Design. The population of this study were all fourth grade students at SD Negeri 097325 Bandar Siantar, totaling 30 students. Because the total population was less than 50, the population was used as the sample in this study. Data collection was carried out by giving tests and observation techniques. The research data was analyzed using descriptive analysis and inferential analysis. Based on the results of data analysis it is known that the results of tcount are 11.27 with a significant level of 0.05. This means that there is an influence of the Problem Based Learning (PBL) Learning Model on Class Student Learning Outcomes IV In Learning Subtheme 3 "Grateful for Diversity" at SD Negeri 097325 Bandar Siantar. This means H1 is accepted and HO is rejected.